The Implementation of Islam as Rahmah Li Al-'Alamin in Indonesia: Contributions, Challenges and Opportunities - Budi Kisworo (AJIS: Academic Journal of Islamic Studies, 2017)
Prophet Muhammad was sent with the teachings of Islam, so Islam is rahmatan lil'alamin.Islam is a blessing for all humans and the nature. In language grace means that tenderness is combined with compassion. In other words, grace can be interpreted with affection. His grace or outpouring of affection is of meaningful and material. The meaningful grace is the enjoyment that comes from being close to Allah SWT, and this is only given to the believers. While the material grace is in the form of physical pleasure and given to all people.So, the Prophet Muhammad saw is the form of Allah's love for all humanity. Islam in Indonesia will not be able to function as rahmatan lil 'alamin as long as the Qur'an is only roled as the five kinds. Islam will serve as rahmatan lil 'alamin only if Muslims want to read the Qur'an, memorize it, teach it to others, understand the content and intentions of its content, put it into national law,respect and obey it.